Health Symptoms and Health Literacy of Pesticides Used among Thai Cornfield Farmers - Taweewun SRISOOKKUM; Ratana SAPBAMRER (Tehran University of Medical Sciences, 2020)
Background: We aimed to explain health symptoms and health literacy on the use of pesticides, investigate predicting factors and to formulate the health literacy model for the appropriate use of pesticides by cornfield farmers in the northern of Thailand. Methods: The reliability and validity from 246 samples were selected by proportional stratified random sampling. Data were collected through a questionnaire in 2016 in Phayao province and were analysed by descriptive statistics and logistic regression. Results:  All of samples exposed from paraquat, the mean years of farm experience were 14.1 yr and five groups of health symptoms from pesticides were muscle and skeleton, epithelial/ mucosal, neurobehavioral, gastrointestinal and endocrine group. The predicting factors had influenced the health literacy of cornfield farmers regarding the use of pesticides were as following: 1) attitude on pesticides exposure (OR= 1.43, CI=1.26-1.64), 2) prevention of the practice of pesticides exposure(OR= 1.03, CI=1.01-1.05) 3) outcome of the expectation on the prevention of pesticides exposure (OR= 0.584, CI=0.41-0.82), 4) the number of secondary occupation(OR= 0.58, CI=0.38-0.89). These affecting factors were considered for the construction of a health literacy model on the use of pesticides. It could predict the model at 42.5%. The health literacy model could be equal to constant (6.85) + attitude on pesticides exposure (0.36) + behavior on the prevention of pesticides exposure (0.03) - outcome expectation on the prevention of pesticides exposure (0.54)- frequency of secondary occupation (0.53). Conclusion: We recommend intervention of attitude, practice, outcome expectation and occupation to set up policy for health services among cornfield farmers.